Design and Build an Industrial Work Practice Presence Information System Using Web-Based GPS - Chesiya Novia Wulandari; Inung Diah Kurniawati; Sekreningsih Nita (TIERS Information Technology Journal, 2022)
The design of this industrial work practice attendance information system can help the SMK Model PGRI 1 Mejayan to speed up the attendance process. This system is designed and built to make it easier for the school to find out the activities and positions of students who are doing industrial work practices by locking latitude and longitude. With the construction of this information system, the attendance process will be more closely monitored and reduce attendance manipulation. The purpose of this study was to determine the design and development of an industrial work practice attendance information system using a web-based GPS (Global Positioning System) at SMK Model PGRI 1 Mejayan. This system development method uses a system development model with the Rapid Application Development method and in its design uses the UML model. The result of this research is an industrial work practice attendance information system using a web-based GPS at SMK Model PGRI 1 Mejayan, and made using the programming language PHP, HTML 5, CSS, Java Script, Code Igniter 3 framework and using the MySQL Database Management System. In making this system using the Visual Studio Code text editor.